2013
DOI: 10.1002/jgre.20060
|View full text |Cite
|
Sign up to set email alerts
|

LRO observations of morphology and surface roughness of volcanic cones and lobate lava flows in the Marius Hills

Abstract: [1] The volcanic domes, cones, sinuous rilles, and pyroclastic deposits of the Marius Hills region of the Moon (~13.4 N, 304.6 E) represent a significant episode of magmatic activity at or near the lunar surface that is still poorly understood. Comparisons between LROC NAC block populations, Mini-RF data, and Diviner-derived rock abundances confirm that blocky lava flows comprise the domes of the Marius Hills. 8 mm features measured by Diviner indicate that the domes are not rich in silica and are not signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 69 publications
2
87
1
Order By: Relevance
“…They had given emphasis on study of morphology of cones having diameters up to 1 to2 km using high resolution LRO-NAC data. Lawrence et al (2013) had also shown the dome analysed in this study as probably associated with Sinous rilles, rille like structure or graben. These types of depressions/structures might be formed due to withdrawal of magma below these regions.…”
Section: Geology Of the Study Areamentioning
confidence: 88%
See 2 more Smart Citations
“…They had given emphasis on study of morphology of cones having diameters up to 1 to2 km using high resolution LRO-NAC data. Lawrence et al (2013) had also shown the dome analysed in this study as probably associated with Sinous rilles, rille like structure or graben. These types of depressions/structures might be formed due to withdrawal of magma below these regions.…”
Section: Geology Of the Study Areamentioning
confidence: 88%
“…Many earlier researchers studied the compositional variations of Marius Hills volcanic Complex (Weitz and Head, 1999;Heather et al, 2003;Besse et al, 2011;Sunshine et al, 1994;Lawrence et al, 2013). Sunshine et al, 1994 identified two units based on the brightness differences in visible and near infrared ratio images (0.76/0.99 lm, a simplified 1 lm band strength).…”
Section: Compositional Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…The atmospheric density ρ air of 0.01 kg/m 3 is chosen to correspond to the present-day conditions on Mars and is corrected for the altitude of Ulysses Colles situated ∼4.5 km above the Martian datum (Brož and Hauber, 2012). The ejected material is assumed to have a uniform density ρ rock of 850 kg/m 3 (Lautze and Houghton, 2005;Harris et al, 2012).…”
Section: Numerical Modelmentioning
confidence: 99%
“…The analysis of recently acquired topographic data from the Lunar Orbiter Laser Altimeter led Spudis (2011) to suggest that the entire Marius Hills complex is a large (330 km across and 3.2 km tall) shield volcano peppered with smaller parasitic vents. Lawrence et al (2013) stated that the Marius Hills represent eruptions of mare materials and the morphological variability was caused by a range of eruption and emplacement conditions. Surrounding the Marius Hills is a high spatial density of sinuous rilles ( Figure 4).…”
Section: Lunar Volcanismmentioning
confidence: 99%